The Formation of Risk Preferences through Small-Scale Events - Silvia Angerer; E. Glenn Dutcher; Daniela Glätzle-Rützler; Philipp Lergetporer; Matthias Sutter (Center for Economic Studies and ifo Institute (CESifo), 2021)
Large, macroeconomic shocks in the past have been shown to influence economic decisions in the present. We study in an experiment with 743 subjects whether small-scale, seemingly negligible, events also affect the formation of risk preferences. In line with a reinforcement learning model, we find that subjects who won a random lottery took significantly more risk in a second lottery almost a year later. The same pattern emerges in another experiment with 136 subjects where the second lottery was played more than three years after the first lottery. So, small-scale, random, events affect the formation of risk preferences significantly.
Keywords: C91; D01; D83; 330; reinforcement learning; risk preferences; preference formation; experiment